1997
DOI: 10.1111/j.1365-2052.1997.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Asian water buffalo (Bubalus bubalis): microsatellite variation and a comparison with protein‐coding loci

Abstract: Twenty-one microsatellite loci in 11 populations of Asian water buffalo (eight swamp, three river type) were analysed and, within and among populations, genetic variability was compared with results from 25 polymorphic protein-coding loci. Within-population mean heterozygosity ranged from 0.380-0.615, approximately twice that estimated from the protein-coding loci (0.184-0.346). Only eight significant departures from Hardy-Weinberg equilibrium (involving four loci) were detected; global tests showed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
137
6
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(164 citation statements)
references
References 22 publications
16
137
6
2
Order By: Relevance
“…than 5% is due to differences among breeds. These values of total genetic differentiation (F ST ) among breeds are close to those found in other domestic species, for example: among river buffalo breeds (F ST = 0.038, Barker et al, 1997), among Spanish horse breeds (F ST = 0.078, Cañ on et al, 2000), though they are slightly lower than those found in Norwegian horse breeds (F ST = 0.12, Bjørnstad et al, 2000), in European cattle breeds (F ST = 0.11, MacHugh et al, 1998;Kantanen et al, 2000) and among Spanish dogs (F ST = 0.099, Jordana et al, 1992). The results from the hierarchical analysis further show that populations of Spanish donkeys are substructured at different levels ( Table 2).…”
Section: Discussionmentioning
confidence: 55%
“…than 5% is due to differences among breeds. These values of total genetic differentiation (F ST ) among breeds are close to those found in other domestic species, for example: among river buffalo breeds (F ST = 0.038, Barker et al, 1997), among Spanish horse breeds (F ST = 0.078, Cañ on et al, 2000), though they are slightly lower than those found in Norwegian horse breeds (F ST = 0.12, Bjørnstad et al, 2000), in European cattle breeds (F ST = 0.11, MacHugh et al, 1998;Kantanen et al, 2000) and among Spanish dogs (F ST = 0.099, Jordana et al, 1992). The results from the hierarchical analysis further show that populations of Spanish donkeys are substructured at different levels ( Table 2).…”
Section: Discussionmentioning
confidence: 55%
“…An evaluation of buffalo genetic diversity along the same lines by Barker et al [3] is also to be mentioned. Once an agreement is reached on a common set of markers, the essential requirements for achieving comparability of allele sizing between different laboratories are (i) to include on the same gel a set of common control DNA samples previously distributed to the participants, and (ii) to preferably use primers derived from a single synthesis, as done in the present experiment.…”
Section: Discussionmentioning
confidence: 99%
“…A subdivisão ou estruturação em espécies de animais domésticos é, geralmente, mais evidente do que em espécies selvagens, devido à separação após serem diferenciadas raças e/ou grupo genéticos geneticamente superiores para uso local, regional ou nacional (1) . Assim, compreender as diferenciações fenotípicas é fundamental para identificar as aptidões específicas entre os grupos genéticos, tendo em vista que, para praticar qualquer tipo de atividade equestre, são necessários equinos com perfil corporal compatível (2,3) .…”
Section: Introductionunclassified